THE COMPETITIVE POSITION OF THE ROMANIAN AGRICULTURE - Croitoru, Gabriel; Mieilă, Mihai; Cicea, Claudiu (Economics of Agriculture, 2018)
The development of the national economy competitive position in the context of the global challenges (global economy, opened international markets, fast changes of technology) is both cause and effect for economic development and for life standards improvement. But, the challenges above mentioned have to be transformed into opportunities for Romanian economy. The identification of impact factors on Romanian agriculture competitive position make necessary a close analysis of economy, of business background, of material and human resources, of costs, of investment activities, and of the innovation process.